Short-term low-volume high-intensity intermittent training improves judo-specific performance - Franchini, E.; Julio, U.; Panissa, V.; Lira, F.; Agostinho, M.; Branco, B. (Archives of Budo, 2016)
Background and Study Aim: An important aspect concerning the specificity principle is related to the time structure of the sport. The aim of our study was the effects of short-term low-volume high-intensity intermittent training (HIIT) added to traditional judo training on physiological and performance responses to judo-specific tasks.